The Legal Status of a Non-Polygamy Agreement Proposed by a Prospective Wife: A Re-reading of QS. An-Nisa Verses 3 and 129 - Indah Ayu Nurkumala; hmad Yusam Thobroni; Abdul Qudus Al-Faruq (al-Afkar, Journal For Islamic Studies, 2026)
The practice of polygamy carried out in the pre-Islamic era greatly degraded the dignity of women, and the Qur'an came down with a revolutionary movement to regulate societal order. Thus, according to Sharia, this practice has legal standing in Islam.  However, on the other hand, there are conditions set by the prospective wife to not be polygamized, which seem to contradict the Sharia. This study is a qualitative research, using a descriptive-analytical approach with the library research method.  The research results show that polygamy is a small emergency door that may be used in extremely urgent conditions, of course with strict conditions.  In the historical context, polygamy was practiced to address social problems such as the protection of orphans' wealth and the protection of widows. Therefore, if polygamy does not function to improve social problems or even creates new social issues, then the practice of polygamy should not be carried out.  Thus, the condition of not practicing polygamy set by the prospective wife can be fulfilled without causing the marriage contract and dowry to be invalidated in the future, provided that the wife can still perform her duties and functions as a wife. Thus, harmony and peace in the household, which are the goals of a marriage, can be realized.